Application of Electronic System Reporting (E-Filling) in the Improvement of Tax Reporting Personal Income - Andi Rustam; Wa Ode Rayyani; Ilham Akbar Wafir (Universitas Muhammadiyah Makassar, 2022)
The study aims to find out (how increased electronic system reporting (e-filling) in personalized income tax reporting) the kind of research used is a qualitative research method. The author's data is the result of interviews to employees, data collection used in this study is observation, interviews and documentaries in which the author goes directly to interview one of watampone's primary system reporting (e-filling) in increasing personal income tax reporting